Konsep Pendidikan Islam dalam Perspektif Muhammad Fethulah Gulen - Sulaiman, Mubaidi (Didaktika Religia, 2016)
The role of education is very important in life. Education is a conscious anddeliberate effort to create an atmosphere of learning and the learning process sothat learners are actively developing the potential for him to have the spiritualpower of religion, self-control, personality, intelligence, character, and skills thatare needed by themselves, society, nation and state. One of the leading figures ineducation from Turky is Fethullah GÃ¼len with his Hizmet, in which science andreligion are to be integrated for all mankind regardless of race, ethnicity, religionand culture. His thoughts are often referred by many thinkers in contemporaryIslamic education as he is known as progressive thinker.